Fingolimod-Associated Intracerebral Lymphoproliferative Disorder. (July 2019) - Baharnoori, Moogeh; Mahajan, Rahul; Solomon, Issac H.; Pinkus, Geraldine; Houtchens, Maria
Abstract : Most epidemiological studies indicate that incidence of cancer in multiple sclerosis patients is lower than general population. However these studies were performed prior to the emergence of disease-modifying therapies (DMTs). The incidence of cancer may be influenced by newer generation DMTs which are immunomodulatory or immunosuppressant. We describe an atypical case of intracerebral plasmacytic lymphoproliferative disorder in a 47 years old patient on fingolimod. As worldwide usage of oral and infusion DMTs increases, heightened clinical suspicion and early recognition of these serious adverse events remain crucial.